Detecting Phishing Attacks using NLP - et. al., Mr.T.H.Feiroz Khan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In present world phishing attacks are the most common and easily targeted attacks. In order to analyse texts and detect improper statements that show the phishing attacks, we have come with an idea which will use (NLP) Natural language processing techniques. Compared to previous work, our approach is different because the emphasis is on the text data found in the attack, which is semanticized in order to identify malicious intent. We have evaluated it using a huge phishing e-mail test data to illustrate the efficacy of our strategy.